Examining the compensation for the 2010 flood in the Sajó valley using real estate examples - Kiss, Alida (Acta Agraria Debreceniensis, 2014)
The intention of this article is to investigate the central damage mitigation of the 2010 flood in point of properties. During the investigationI performed the processing of the revealed data on a country level perspicuity, and in details on the level of sample area. In my study I worked with the available damage summations, the number of the damaged properties and the sources granted by central budget to extenuate those,and the husbandry database comparative analysis of local government of the sample strata. It came clear by the analysis of the results, which regions require more acquisition in the further process of the project.